2017
DOI: 10.29312/remexca.v8i18.211
|View full text |Cite
|
Sign up to set email alerts
|

Diversidad y abundancia de bromelias epifitas en “El Punto” Santa Catarina Ixtepeji, Oaxaca

Abstract: Las bromelias son plantas que crecen en bosques y selvas del continente americano. En México las bromelias reportadas sobrepasan las 363 y Oaxaca posee 189 de ellas. El municipio de Ixtepeji y sus agencias incluido “El Punto” en Oaxaca, aprovechan bromelias epifitas. Desde el año 2008 cuentan con una UMA, donde sus integrantes recolectan en zonas específicas. Con el objetivo de determinar la diversidad y abundancia de bromelias como indicadores ecológicos del manejo del bosque, se realizó, durante 2015, un mue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…After decades of timber extraction, the Sierra Norte still has the highest biodiversity in birds, mammals, and amphibians in Mexico (Brandon et al, 2005;Illodi-Rangel et al, 2008), and new species are regularly found (Canseco-Márquez et al, 2017). Timber extraction is compatible with conservation of epiphytic bromeliads, including threatened species like Tillansia carlos-hankii and endemics such as T. oaxacana (Carvente-Acteopan et al, 2017). In Chiapas, Ballam-Ballote and León-Cortés (2010) showed that community managed forests increase landscape heterogeneity, contributing to greater butterfly diversity.…”
Section: Reducing Deforestation and Conserving Biodiversity In Mexica...mentioning
confidence: 99%
“…After decades of timber extraction, the Sierra Norte still has the highest biodiversity in birds, mammals, and amphibians in Mexico (Brandon et al, 2005;Illodi-Rangel et al, 2008), and new species are regularly found (Canseco-Márquez et al, 2017). Timber extraction is compatible with conservation of epiphytic bromeliads, including threatened species like Tillansia carlos-hankii and endemics such as T. oaxacana (Carvente-Acteopan et al, 2017). In Chiapas, Ballam-Ballote and León-Cortés (2010) showed that community managed forests increase landscape heterogeneity, contributing to greater butterfly diversity.…”
Section: Reducing Deforestation and Conserving Biodiversity In Mexica...mentioning
confidence: 99%
“…Para El Punto, Oaxaca, el heno (Tillandsia usneoides) es una bromelia de gran importancia para las integrantes de la Unidad de Manejo de la Vida Silvestre (UMA), especialmente en temporada "navideña" (Mondragón-Chaparro, Villa-Guzmán, Escobedo-Sarti y Franco-Méndez, 2006 y Carvente-Acteopan, Pérez-Olvera, Flores-Cruz, Navarro-Garza y Flores-Hernandez, 2017) siendo una especie muy abundante en dos de las cuatro zonas de recolección con las que cuenta la comunidad (Carvente et al, 2017).…”
Section: Introductionunclassified